(untitled) (Experimental biology, 2018)
One of the most urgent problems is the conservation of rare, endemic and endangered plant species. The main goal of the research is to study the cenopopulations of the rare species Anthemis trotzkiana Claus (Asteraceae) in the Aktobe region. The work defines the territory of distribution of Anthemis trotzkiana Claus populations in the Aktobe region, as a result of geobotanical studiestheir current state was assessed. The geographical location of the 3 Anthemis trotzkiana Claus populations in the Aktobe region (Akshatau, Beshtau, Ishkarahantau) was determined, and a complete list of the floral composition of plants found in 9 cenopopulations is presented.18 families belonging to 36 genera and 40 species are defined on the territory of the studied 3 populations. On the territory of distribution of the first population there are 20 species belonging to 19 genera of 12 families. The second population consists of 19 species related to 18 genera of 12 families.The floristic composition of the area of the third defined population includes 21 species of 19 genera and 13 families. There were identified 8 speciesfound on the territory of all three populations (Allium globosumBieb. ex Redoute., Gypsophila diffusa Fisch. &C.A.Mey. ex Rupr., Zygophyllum macropterum C. A. Mey. = Z. pinnatum, Trinia hispida Hoffm., Linaria cretacea Fisch. ex Spreng., AnthemistrotzkianaClaus, Artemisia salsoloidesWilld., Centaurea sibirica L.).Species from the Asteraceae familyare considered as dominant in there searchareas. We were determined first of the geographical location of Limonium cretaceum Tscherkasova belonging to the first population, which grows on the territory of Akshatau and Pimpinella titanophila Woronow. = P. tragium belonging to the third population found in the territory of Ishkargantau firstly. Previously, these plants were not registered in the floristic composition of the Aktobe region.